New Distributional Record of Urentius hystricellus (Richter, 1870) (Hemiptera: Tingidae) from Southernmost Region of Punjab, Pakistan: Lace bug from Southern Punjab, Pakistan - Rasheed, Muhammad Tariq; Imran Bodlah; Muhammad Qurban; Muhammad Bilal Khalil; Muhammad Usama Khalil; Junaid Ali Siddiqui; Ammara Gull E Fareen; Muhammad Adnan Bodlah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Urentius hystricellus is well known phytophagous and invasive true bug of family Tingidae. From Pakistan, this family is poorly studied despite having significant economic importance. Present species was identified with the help of most relevant and published literature. Specimens were mounted on triangular cards for morphological studies. New distributional data of U. hystricellus is included. Brief diagnosis, host plant and remarks on biology and current distribution in Pakistan are added. Line drawing of adult and fore wing along with digital photographs are also given.